Parental mental health during COVID-19 pandemic in Tamil Nadu: a cross sectional study - R., Hari Krishnan; Rajasekar, Hanitha; S., Suganthi (International Journal Of Community Medicine And Public Health, 2021)
Background: The whole world became still, when a major pandemic COVID-19 started its toll across all developed and developing countries. It has caused both physical and emotional disturbances among all age groups. This study was done to evaluate the parental mental health in COVID-19 as this group is not given much importance. The major mental health problems associated with COVID-19 among parents are due to online classes which has caused depression, anxiety and stress. Methods: A cross-sectional study done among all parents, especially those of whose children are attending online class were included in the study. Convenient sampling was used to select 204 participants, GHQ 12 questionnaire was used for data collection on mental health status among parents. Results: Overall prevalence of parents with better mental health <19 was 108 (52.9%) and prevalence of parents with poor mental health >19 was 96 (47.1%). Conclusions: This study concluded that parental age of 31 to 40 years who are employed and have children studying in primary school to have a poor mental health status. The most important contributing factors for poor parental health were online classes for children and work place stress.